2008
DOI: 10.1021/bi800650w
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Histidine 351 in the Reaction of Alcohol Oxidation Catalyzed by Choline Oxidase

Abstract: Choline oxidase catalyzes the four-electron, flavin-linked oxidation of choline to glycine betaine with transient formation of an enzyme-bound aldehyde intermediate. The recent determination of the crystal structure of choline oxidase to a resolution of 1.86 A established the presence of two histidine residues in the active site, which may participate in catalysis. His466 was the subject of a previous study [Ghanem, M., and Gadda, G. (2005) Biochemistry 44, 893-904]. In this study, His351 was replaced with ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 19 publications
(74 reference statements)
8
74
0
Order By: Relevance
“…In this regard, previous results with a substrate analog devoid of positive charge demonstrated that it is the positive charge harbored on the trimethylamine group of the enzyme-bound betaine aldehyde that plays an important role for oxygen reactivity in choline oxidase (49,51). In agreement with the lack of involvement of ionizable groups in the oxidative half-reaction is the observation that no pK a values in the range between 7.0 and 11.0 were detected in the pH profile of the k cat /K oxygen value with the H99N enzyme, as also was previously reported for the H351A and H466A forms of choline oxidase (55,56).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this regard, previous results with a substrate analog devoid of positive charge demonstrated that it is the positive charge harbored on the trimethylamine group of the enzyme-bound betaine aldehyde that plays an important role for oxygen reactivity in choline oxidase (49,51). In agreement with the lack of involvement of ionizable groups in the oxidative half-reaction is the observation that no pK a values in the range between 7.0 and 11.0 were detected in the pH profile of the k cat /K oxygen value with the H99N enzyme, as also was previously reported for the H351A and H466A forms of choline oxidase (55,56).…”
Section: Discussionsupporting
confidence: 87%
“…Unlike the wild-type (38,51,54) and other choline oxidase variant enzymes (12,55,56), which contain a mixture of oxidized flavin and air-stable, anionic flavosemiquinone upon purification, the H99N mutant enzyme was purified with the bound flavin cofactor in the fully oxidized state, as indicated by the UV-visible absorbance spectrum showing absorbance maxima at 390 and 450 nm (supplemental Fig. S1).…”
Section: Purification and Biochemical Characterization Of Cho-h99n-mentioning
confidence: 99%
“…In glucose oxidase, effective oxidation of the reduced flavin was proposed to require an active site histidine with pK a of 7.9 to be protonated (50,52). In choline oxidase, oxidation of the reduced flavin is facilitated by the non-dissociable, positively charged trimethylammonium moiety of the choline substrate but not by ionizable groups in the active site of the enzyme (43,(53)(54)(55). In GOX, one can immediately rule out the ionization of the flavin hydroquinone species as being responsible for the pK a value of 6.8, since the UV-visible absorbance spectra of the reduced enzyme after anaerobic reaction with glyoxylate, with well resolved maxima at ϳ340 nm, strongly support the notion that the hydroquinone species is in the anionic state between pH 6.0 and 10.0 (56).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in pK a for Glu 312 , compared with that for Glu 389 in AAO, drastically increases the energy barrier and intermediate energies for the second histidine path in CHO, the His 351 -Glu 312 path. Although the studies of Gadda and co-workers [10,12] have not definitively concluded the nature of the CHO base, mutation of His 466 has the larger effect on k cat . More recently, Gadda [8] suggested that either one of the active-site histidine residues in CHO (His 351 and His 466 ) act as the base (being replaced by the second histidine residue when mutated) or, alternatively, the acidification of the substrate hydroxy group and proton loss to the solvent may occur through interactions with multiple active-site residues.…”
Section: Catalytic Mechanisms In Gmc Oxidoreductases: a Comparison Bementioning
confidence: 96%
“…Mechanistic studies based on substrate KIEs (kinetic isotope effects) in CHO and methanol oxidase proposed the existence of two distinct steps in the reductive halfreaction, with the rate-limiting step being the hydride transfer from a protein-stabilized substrate alkoxide [8,9]. Mutational studies on CHO [10][11][12] have aimed to address the role of the active-site residues in the catalytic process. Both His 466 and His 351 are important for the alcohol proton abstraction, although there is The FAD isoalloxazine ring and five active-site residues are shown (as CPK sticks).…”
Section: Introductionmentioning
confidence: 99%